The Influence of the Covid-19 Pandemic on Economic Growth Convergence at the District/City Level in East Java: What Is the Right Public Policy? - Verianto, Mohammad Ichsan; Faiq, Muhammad Nur; Aisyah Tarassyta (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
Indonesia has experienced relatively significant and stable economic growth in the last decade. However, Indonesia, a developing country, is still vulnerable to income disparities between regions or regions. It is due to the unequal distribution of natural resources, population, and development concentration. This study aims to examine the effect of the COVID-19 pandemic on the convergence of economic growth in East Java Province. In this study, per capita Gross Regional Domestic Product (GRDP) data or secondary data with panel type is used which is accessed from the annual report of the Central Statistics Agency in each district or city in East Java for the period 2010 to 2020. By using the -convergence analysis technique and -convergence and considering the spatial dependence between regions, the researchers found no substantial evidence of the occurrence of regional income convergence in East Java. There has been a divergence in regional income before and after the pandemic. But with a more significant divergence coefficient before the pandemic, it means that the existence of a pandemic has reduced the level of divergence even though the catch-up effect is negligible on economic growth. In general, this means a decrease in income inequality due to the pandemic, as rich regions are affected more than poor regions. So that public policy recommendations are needed, especially after the pandemic, through recovery that focuses on improving the economic sector in the affected affluent areas such as Surabaya and others.